Dominic Nagle: capstone - Nagle, Dominic, artist (Colorado State University. Libraries, 2022)
The artist's statement: Process is my favorite part of designing. Even though the final product is the most important and is what really matters, my hands-on technique keeps me obsessed with my work. Drawing, cutting and scanning are my main tools to create gripping designs. Vintage compositions such as old punk posters, signs on the streets and graphic t-shirts are heavy inspirations and keep me constantly constructing new ideas. In the end I just create designs that can provoke visual impressions from the viewer which I believe graphic design is all about.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design